2021 Asia Pacific Heart Rhythm Society (APHRS) practice guidance on atrial fibrillation screening. Issue 1 (28th December 2021) - Chan, Ngai‐Yin; Orchard, Jessica; Agbayani, Michael‐Joseph; Boddington, Dean; Chao, Tze‐Fan; Johar, Sofian; John, Bobby; Joung, Boyoung; Krishinan, Saravanan; Krittayaphong, Rungroj; Kurokawa, Sayaka; Lau, Chu‐Pak; et al.
Abstract : In this paper, the Asia Pacific Heart Rhythm Society (APHRS) sought to provide practice guidance on AF screening based on recent evidence, with specific considerations relevant to the Asia‐Pacific region. A key recommendation is opportunistic screening for people aged ≥65 years (all countries), with systematic screening to be considered for people aged ≥75 years or who have additional risk factors (all countries).